The Influence Of Level Of Disclosure On Brand Evaluation And Brand Recall With Psychological Trait Reactance And Program Involvement As Moderator Variables And Program Liking As Intervening Variables (Study On Subway Placement Products In The Korea Drama - Ifada, Shafa Radisya Aulia; Widodo, Teguh (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2024)
This research is motivated by product placement, which serves as an alternative to traditional advertising usually broadcasted on mass media and frequently used in Korean dramas. Given the popularity of Korean dramas among international audiences, global brands have sought to participate in such product placement activities. However, there are instances where viewers complain about excessive and unreasonable product placements that disrupt their engagement due to their frequent appearances. The purpose of this study is to examine the impact of level of disclosure (LoD) on brand recall (BR) and brand evaluation (BE), while considering the moderating effects of psychological trait reactance (PTA) and program involvement (PI), with program liking (PL) acting as a mediating variable. The study focuses on subway product placement in the Korean drama "Descendants of the Sun" (DoTS). The research utilized a sample of 400 respondents who had watched the DoTS drama and had observed the subway product placement within the show. The results indicate that LoD indeed affects BR and PL. Moreover, PL significantly and positively mediates the relationship between LoD and BE. Based on the findings, this study recommends product owners aiming to advertise their products through dramas to select shows featuring well-known characters and enjoying high ratings. This strategy will likely attract more audience attention to their products.